Pumpkin - Murphy, Julie, 1985- (Balzer + Bray, an imprint of HarperCollinsPublishers, 2021)
Creating a drag-show audition tape that culminates in an unkind nomination for prom queen, an overweight and openly gay teen partners with a girl who has been nominated for prom king to embrace their true selves.